Boundary-Value Problem with Impulsive Conditions and Degeneration for Parabolic Equations - Isaryuk, I. M.; Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We consider the second boundary-value problem for a parabolic equation with power singularities in the coefficients of space variables and impulsive conditions in the time variable. By using the maximum principle and a priori estimates, we establish the existence and uniqueness of the solution of posed problem in Hölder spaces with power weights.